Arqueologia de um naufrágio em Neópolis: materialidade de um conflito no Baixo São Francisco - Martins, Thor Gabriel (2025)
This dissertation examines the submerged archaeological site “Naufrágio de Neópolis,” located on the bed of the São Francisco River in Sergipe, Brazil. The research seeks to understand the site’s formation process through the material remains of the shipwreck, interpreted from the perspective of conflict archaeology. The aim is to contextualize the find within the political-military and economic dynamics that shaped the Lower São Francisco between the late 18th and 19th centuries. To this end, an analytical model is proposed for the study of submerged contexts associated with conflicts, integrating structural and naval analyses, laboratory results, and cross-referencing with historiographical sources. This approach makes it possible to discuss the strategic use of river routes and the local specificities reflected in the recorded materiality. Understood as direct evidence of broader historical processes, the site provides valuable insights for social, economic, and political interpretations of the region, highlighting its role in colonial and postcolonial developments. Furthermore, its investigation contributes to strengthening underwater archaeology as a tool for interpreting national history.